Tantangan Dan Strategi Penyuluhan Agama Kristen Dalam Pelaksanaan Program Penyuluhan Selama Masa Pandemi Covid Di Kabupaten Tapanuli Utara - Enda Dwi Karina Perangin-angin; Hanna Dewi Aritonang; Tiur Imeldawati; Damayanti Br Hombing (Institut Agama Kristen Negeri Tarutung, 2022)
Abstract:Counselling given by Christian counsellors is a form of service provided to the community. In this research, the researcher tried to formulate several research questions, including what are the challenges faced by Christian counsellors in the North Tapanuli district? What are the strategies used by Christian counsellors in implementing counselling programs during the pandemic? What is the relevant counselling strategy that can be implemented in the COVID-19 pandemic? The purpose of this study was to reveal challenges experienced by Christian counsellors in the North Tapanuli region. From this research, the description of challenges experienced by Christian counsellors was obtained, as well as the strategies that had been implemented in doing counselling during the COVID-19 pandemic. The highlight of this study was to find the most relevant strategy or model of counselling to the context of North Tapanuli that can be applied by Christian counsellors. The methodology used in this research was a qualitative method. From the research conducted, it was found that there are three weaknesses of the Christian counsellors of North Tapanuli, such as: first, there is no module for each counselling target area. Second, the lack of religious counselling strategy, and third, the lack of coordination between Christian counsellors and the local government. The threats or challenges experienced by Christian counsellors such as: first, the pandemic situation that is not over yet. Second, the limitations of the certain community group in using technology. Third, the time management, in this case, the majority of the community are farmers and spend most of their time in the fields. Fourth, the public's perception of Christian counsellors that there is a lack of appreciation from the community for Christian counsellors, especially those with non-civil servant status.Keywords: counsellor, counselling challenges, counselling strategies Abstrak:Penyuluhan yang diberikan oleh para penyuluh agama Kristen merupakan bentuk layanan yang diberikan kepada masyarakat. Dalam riset ini, peneliti berupaya merumuskan beberapa pertanyaan penelitian antara lain apa saja tantangan yang dihadapi para penyuluh agama di kabupaten Tapanuli Utara ini? Bagaimana strategi penyuluh agama dalam melaksanakan program penyuluhan selama masa pandemi? Apakah strategi penyuluhan yang relevan di tengah pandemi covid-19? Adapun tujuan penelitian ini adalah untuk mengungkapkan tantangan apa saja yang dialami oleh para penyuluh agama yang ada di wilayah Tapanuli Utara. Dari penelitian ini diperoleh deskripsi tentang tantangan yang dialami oleh penyuluh, sekaligus juga untuk mengetahui strategi apa yang telah mereka lakukan dalam melaksanakan pembinaan kepada masyarakat selama masa pandemi covid-19. Puncak kajian ini diharapkan menemukan strategi atau model pembinaan yang paling relevan dengan konteks Tapanuli Utara yang dapat diaplikasikan oleh penyuluh agama Kristen. Metodologi yang dipakai dalam riset ini adalah metode kualitatif. Dari penelitian yang dilakukan didapati bahwa ada tiga hal yang menjadi kelemahan dari pelayanan penyuluh agama Kristen di Tapanuli Utara ini antara lain: pertama, tidak adanya modul untuk setiap bidang sasaran penyuluhan. Kedua, minimnya strategi penyuluhan agama dan ketiga, kurangnya koordinasi antara penyuluh agama Kristen dengan pemerintah setempat. Adapun ancaman atau tantangan yang dialami antara lain: pertama, situasi pandemi yang belum usai. Kedua, keterbatasan warga binaan dalam memanfaatkan teknologi informasi. Ketiga, permasalahan waktu, karena mayoritas pekerjaan masyarakat adalah bertani dan menghabiskan waktu di lading. Keempat, anggapan masyarakat terhadap penyuluh agama dimana kurang adanya penghargaan dari masyarakat terhadap penyuluh agama Kristen khususnya yang berstatus non PNS. Kata kunci: penyuluh, tantangan penyuluh, strategi penyuluhan